The late tenth-century defences of Oxford and the towers of St George and St Michael. Issue 2 (3rd July 2021) - Haslam, Jeremy
ABSTRACT: The hypothesis of the redevelopment of the defences of the earlier burh at Oxford by King Æthelred in the late tenth century is critically analysed in the light of the recently-published excavations at the castle site. It is argued that the rebuilding of the north gate, which involved the creation of a new defended enceinte on its eastern side and the construction of the tower of St Michael's Northgate, was concurrent with, and as an integral part of, this new defensive initiative. St George's tower, which sits within the western line of these late tenth-century defences, is also argued from the structural and topographical evidence as belonging to this same phase of the reconstruction of the defences. This is supported by comparisons of the towers' architectural features with other church towers in England, and reflects similar developments in northern France. The evidence of this new defensive system from Oxford complements and extends the historical and other evidence from the country as a whole, providing a revealing insight into the scale and nature of the strategic response of King Æthelred to the new Viking incursions during his reign.